Deer velvet antler water extract demonstrates non-cytotoxic effects and maintains viability of dental stem cells - Azami, Azalea Nur-Qistina; Mokhtar@Makhtar, Khairani Idah; Mustafa Al-Ahmad, Basma Ezzat; Mohd Kenali, Norzaiti; Sha'ban, Munirah; Ahmad, Azlina; Zainol, Ismail (Ectodermal Dysplasia Group-Turkey, 2025)
Deer velvet antler (DVA), widely used in traditional Asian medicine, is gaining research interest for its effects on bone health, tissue regeneration, and cancer. However, the fundamental analysis looking into the effects of DVA on stem cells; particularly derived from dental tissues, are limited. Hence, this research aims to determine the biological effects of DVA water extract on the viability of stem cells harvested from human exfoliated deciduous teeth (SHED). DVA water extract was subjected for small molecule compounds analysis using LC-MS/MS-QTOF. The effects of DVA water extract on SHED were assessed at concentration up to 200 μg/ml for cell viability using MTT assay, cell morphology using inverted microscope and proliferative activity described as population doubling time (PDT) using alamarBlue assay. Although insignificant, DVA water extract at 3.125 μg/ml produced the lowest PDT while maintaining the cell proliferation and viability. Overall, DVA water extract at concentration up to 200 μg/ml was not cytotoxic, maintained its proliferative effects and the morphology of SHED. The presence of detectable small molecules in water extract which corresponds to the multiple benefits of DVA might be responsible for the demonstrated observations.